PERBANDINGAN METODE TITRASI DAN FOURIER-TRANSFORM INFRARED (FTIR) DALAM PENENTUAN BILANGAN ASAM MINYAK ZAITUN - Azmi, Ulil
Olive oil contains triacylglycerol consisting of mainly oleic acid mono-unsaturated fat. Acid value determination was usually done using the KOH/NaOH acid-base titration method. Acid value was determined as the amount of KOH in mg needed to neutralize free fatty acid in 1 gram of sample. In the oil structure, carboxylic acid functional group was detected from free fatty acid measured using FTIR so the acid value can be determine. Olive oil heating was done for 0, 2, 4, 6, 8, 10, and 12 hours at 120 o C to vary the acid value. The acid value of every olive oil was measured using KOH titration method with phenolphthalein indicator. Calibration curve of oleic acid was made from 1430.92 –1342.31 cm -1 and 1338 –1218.79 cm -1 wavenumber spectra area, which was derived spectrum; 1770.33 and 3463.53 cm -1 cm- 1 from the absorbance spectrum. Measurements of every heated olive oil were done using FTIR and resulted in the total oleic acid of each sample. The acid value from FTIR was obtained by multiplying the amount of oleic acid with its acid value. The acid values from FTIR at each wavenumber were compared statistically using paired T student with acid value obtained from titration method. Results showed that there were no meaningful differences between acid value obtained from FTIR in 1338 - 1218.79 cm -1 and 3463.53 cm -1 wavenumber with acid value obtained from titration method.